Tinjauan Siyasah Tanfidziyyah Terhadap Implementasi Peraturan Daerah (Perda) Kabupaten Pesawaran Nomor 11 Tahun 2015 Tentang Pelayanan Publik Pada Layanan Air Bersih Oleh Pdam: Studi Di Desa Hanau Brak Kecamatan Padang Cermin Kabupaten Pesawaran - Zahrotun Annisa; Zuhraini; Nurasari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the implementation of Pesawaran Regency Regional Regulation Number 11 of 2015 concerning Public Services in the provision of clean water services by the Regional Water Supply Company (PDAM) in Hanau Brak Village, Padang Cermin District, and examines it from the perspective of Siyasah Tanfidziyyah. The study employs a qualitative approach using field research methods through observation, interviews, and documentation, with data analyzed descriptively and analytically. The findings reveal that the implementation of clean water services has not been optimal due to aging and leaking pipeline infrastructure, unstable water distribution, an ineffective complaint-handling mechanism, and weak coordination between PDAM and the village government. Perspective of Siyasah Tanfidziyyah, these conditions indicate that the principles of amanah (trustworthiness), justice, and maslahah (public welfare) have not been fully realized. This study recommends the rehabilitation of the pipeline network, the strengthening of a responsive complaint-handling system, and improved coordination between PDAM and the village government to ensure that clean water services comply with regional regulations and the principles of Islamic law.